Factors Supporting Community Participation In Waste Management As An Additional Source Of Income - Fachruddin Arrozi; Amrizal Amrizal (Cita konsultindo, 2024)
This study examines how environmental literacy, Islamic Social Entrepreneurship (ISE), community support, and policy socialization impact community participation in waste management at TPS-3R Tambakrejo, Waru, Sidoarjo. Using a descriptive quantitative approach with 162 respondents and SEM analysis, the study finds that environmental literacy does not significantly influence participation (t=0.257, p=0.798). However, ISE positively impacts participation (t=1.877, p=0.016), while community support (t=4.624, p=0.000) and policy socialization (t=2.719, p=0.007) have significant positive effects. These findings highlight the need for strategies that leverage ISE, community support, and effective policy socialization to improve waste management participation based on Islamic finance principles. These findings provide valuable insights for policymakers, practitioners, and researchers in developing effective strategies to enhance community participation in waste management programs based on Islamic finance principles that emphasize sustainability, social justice, and economic welfare.